Spatiotemporal characterization of meteorological drought and rainfall variation during El Niño/La Niña event over Bundelkhand region of India - V. S. Yadav; R. V. Galkate; V. K. Chandola; Anoop Kumar Shukla; Samikshya Panda; Satyavati Shukla (Discover Applied Sciences)
Abstract This study analyzes the relationship between the El Niño-Southern Oscillation (ENSO) and rainfall variability in the Bundelkhand region using the Oceanic Niño Index (Niño 3.4 Index) for the period 1950–2022. Drought monitoring was conducted using the Standardized Precipitation Index (SPI) to assess the impact of ENSO on regional drought conditions. Results indicate that El Niño years correspond to a decline in rainfall, with weak and moderate El Niño events leading to deficits of − 38.62 mm and − 21.44 mm, respectively, while strong El Niño years experienced a significant reduction of − 128.8 mm. Conversely, the relationship between La Niña and rainfall is inconsistent, with moderate La Niña years showing a positive anomaly of 66.89 mm, while weak and strong La Niña years resulted in mixed effects, with anomalies of − 17.59 mm and − 56.72 mm, respectively. Spatiotemporal analysis further revealed that drought conditions persisted in Bundelkhand during the La Niña years of 1973 and 2020, highlighting the region’s unique response to ENSO events. These findings emphasize the need for localized climate assessments, as large-scale ENSO trends do not consistently predict rainfall patterns in Bundelkhand region. This study provides valuable insights for drought mitigation and early warning strategies in the region.